2018
DOI: 10.1016/j.healun.2017.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Influence of various therapeutic strategies on right ventricular morphology, function and hemodynamics in pulmonary arterial hypertension

Abstract: In advanced treatment-naive IPAH patients, an upfront combination therapy strategy seems to significantly improve hemodynamics and RV morphology and function compared with oral monotherapy. The most significant results seem to be achieved with prostanoids plus oral drug, whereas the use of the double oral combination and prostanoids as monotherapy seem to produce similar results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 35 publications
(34 reference statements)
7
46
0
Order By: Relevance
“…Our findings are aligned with those from previous randomised controlled trials and real-world studies where haemodynamic and functional improvement was observed following initial ERA and PDE5i combination therapy [1,[8][9][10][11][12]. Safety and tolerability were generally consistent with previous data for macitentan in combination with PDE5i [5,6,13].…”
Section: To the Editorsupporting
confidence: 90%
“…Our findings are aligned with those from previous randomised controlled trials and real-world studies where haemodynamic and functional improvement was observed following initial ERA and PDE5i combination therapy [1,[8][9][10][11][12]. Safety and tolerability were generally consistent with previous data for macitentan in combination with PDE5i [5,6,13].…”
Section: To the Editorsupporting
confidence: 90%
“…Right ventricular function is a critical outcome determinant in patients with PH. An association between RV function and survival has already been described in patients with PAH treated with specific therapy [21][22][23]. We speculate that this could be also applicable for CTEPH patients treated with BPA.…”
Section: Effect Of Bpa On Clinical Outcomesupporting
confidence: 59%
“…this context, it is noteworthy that previous observational studies have shown a much more impressive therapeutic response when the intravenous prostacyclin therapy was initiated in treatment-naïve patients as part of an upfront combination regimen. 22,23 In contrast, late initiation of intravenous prostacyclin therapy was an independent predictor of a poor outcome in a series from Italy. 24 Taken together, these observations favor early initiation of intravenous therapy, but further studies are needed to better determine when this treatment should be initiated and which patients benefit most.…”
Section: Discussionmentioning
confidence: 86%